Bringing Student-Generated Comic as a Collaborative Project into the Extensive Reading Program - Novita, Dian; Setiawan, Slamet (Universitas Muhammadiyah Sidoarjo, 2020)
The study looks into the possibility of bringing student-generated comic as a collaborative project into the Extensive Reading program. It focuses on the students’ preferences and difficulties in creating a student-generated comic based on their perceptions. For this purpose, the study involved 30 students of the English Education Program of Universitas Muhammadiyah Sidoarjo, who had taken the Extensive Reading program. The questionnaire is employed to assess their perceptions. The results of the study show that creating a student-generated comic is a pleasurable doing, an exciting activity, and a fun way for the EFL learners to study English. Moreover, students consider that student-generated comics can improve students’ language production creativity, contribute an educational resource for other students, and arouse their creativity. Concerning the development of students’ language proficiency, creating comic corresponds to the novel they have studied, affects their English fluency, and improves their writing skills. Astonishingly, only a few students believe that it is not easy to draw and illustrate a comic, compose stories and characters, and reveal the novel’s aspects into a comic. HIGHLIGHTS: Creating a student-generated comic collaboratively as one of Extensive Reading activities is enjoyable, and it is a motivating activity for the students to learn and practice English. Generating the comic collaboratively can affect students’ English fluency, understand the novel’s content quickly, and improve their writing skill. It is important for combining the curriculum of adult ESL with educational comics to promote the students’ skills and concepts involved in a broad range of literacy.